1996
DOI: 10.1016/s1078-5884(96)80175-4
|View full text |Cite
|
Sign up to set email alerts
|

Secondary aortoenteric fistulae — Changes from 1973 to 1993

Abstract: Over a 21 year period there seems to have been a decrease in the frequency of secondary aortoenteric fistulas after aneurysm surgery, a longer interval before they occur, a shorter diagnostic delay, and a better survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 6 publications
3
25
0
5
Order By: Relevance
“…Previous studies done in this hospital have demonstrated that a high risk of developing infection and anastomotic aneurysm exists when Dacron prostheses are used, and that use of these devices is associated with some deaths; the second most frequent cause of late death is complications related to the use of prosthetic graft 6,7,9,57,58 . The same results are reported from different vascular centers [59][60][61][62][63][64] . Raptis et al (1995) report a 1% per year postsurgical complication rate associated with aortofemoral bypass for up to 10 years after surgery 65 .…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies done in this hospital have demonstrated that a high risk of developing infection and anastomotic aneurysm exists when Dacron prostheses are used, and that use of these devices is associated with some deaths; the second most frequent cause of late death is complications related to the use of prosthetic graft 6,7,9,57,58 . The same results are reported from different vascular centers [59][60][61][62][63][64] . Raptis et al (1995) report a 1% per year postsurgical complication rate associated with aortofemoral bypass for up to 10 years after surgery 65 .…”
Section: Discussionsupporting
confidence: 82%
“…Diagnosis of aorto-enteric fistulae can be difficult (39). If untreated, this condition is always fatal.…”
Section: Aorto-enteric Fistulaementioning
confidence: 99%
“…The placement of a feeding jejunostomy at the time of operation should also be considered (Chenu 2009). The risk of secondary rupture of the abdominal aorta following treatment for an aortoenteric fistula has been reported as being between 9 and 17% (Kuestner et al, 1995;Menawat et al, 1997;Bergqvist et al, 1996). These figures add to the significant overall mortality risk associated with this complication.…”
Section: Managementmentioning
confidence: 99%